Assessment and Management of Over-Activity and Sleep Disorder in Mucopolysaccharidoses - Hare, Dougal Julian; Mahon, Louise; Rust, Stewart (Journal of Child Science, 2018)
There is a growing awareness, based on both research and clinical studies, that abnormal sleep and circadian functioning are associated with the various forms of mucopolysaccharidoses (MPS), with sleep respiratory problems seemingly common in many forms of MPS. In the case of MPS III, there is evidence of syndrome-specific sleep disturbance related to an abnormal and possibly unique circadian rhythm. The presence of such patterns of sleep and activity has detrimental consequences for both the person with MPS and also invariably for her/his family and carers. On the basis of current evidence, routine assessment of sleep functioning is clearly warranted for all children with MPS III together with appropriate medical and behavioral interventions as required.
Keywords: mucopolysaccharides; Sanfilippo syndrome; sleep; circadian; activity